2013
DOI: 10.1016/j.ijid.2013.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Multifocal tuberculosis verrucosa cutis of 60 years duration

Abstract: Figure 1. The oldest lesions were in the knee area and had spread progressively over a duration of approximately 60 years; (a) before treatment, (b) after treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 5 publications
0
7
0
Order By: Relevance
“…The lesions of verrucous TB are single, painless, and in areas that are prone to traumas, as occurred in our patients with leg or foot injury background (Fig. ) . Historically, they are related to handling infectious material, especially in some professional groups, and also attributed to walking barefoot …”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…The lesions of verrucous TB are single, painless, and in areas that are prone to traumas, as occurred in our patients with leg or foot injury background (Fig. ) . Historically, they are related to handling infectious material, especially in some professional groups, and also attributed to walking barefoot …”
Section: Discussionmentioning
confidence: 65%
“…6). [45][46][47][48] Historically, they are related to handling infectious material, especially in some professional groups, and also attributed to walking barefoot. 2,36,49 Our group tend to regard a granulomatous lobular or septolobular panniculitis (with or without vasculitis) in the setting of a clinical, epidemiological, and/or microbiological diagnosis of tuberculosis as EIB, which was an important clinical form in our study.…”
Section: Discussionmentioning
confidence: 99%
“…The overall sensitivity was found to be 73%. 15 A recent study from India showed that the sensitivity of DNA PCR is 25% in the diagnosis of cutaneous tuberculosis [12] [In the event of inconclusive specific tests, the diagnosis is based on correlation between clinical appearance and histopathological findings along with clinical response following antituberculous treatment [13] To the best of our knowledge only two such cases of multifocal tuberculosis verrucosa cutis had been reported earlier in immunocompetent and otherwise healthy individuals [14,15]. Prasad et al in 2002 reported a similar case with multifocal involvement but the patient had microcytic normochromic anemia with a hemoglobin 5.6 g% [16].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, although the mechanism of pathogenesis remains uncertain, the most plausible explanation of our patient's case would be exogenous inoculation. Although the habitat for mycobacteria in this case is unusual, it is not without precedent because cases of cutaneous TB have been described in individuals from merely walking barefoot with minimal trauma [ 10 – 12 ] in endemic countries. A specific case was published in 2005 in which a 13-year-old boy from the Colombian Amazon was diagnosed with cutaneous TB by PCR and culture.…”
Section: Diagnosismentioning
confidence: 99%